2017
DOI: 10.1177/1535370217693117
|View full text |Cite
|
Sign up to set email alerts
|

Association between red meat consumption and colon cancer: A systematic review of experimental results

Abstract: A role for red and processed meat in the development of colorectal cancer has been proposed based largely on evidence from observational studies in humans, especially in those populations consuming a westernized diet. Determination of causation specifically by red or processed meat is contingent upon identification of plausible mechanisms that lead to colorectal cancer. We conducted a systematic review of the available evidence to determine the availability of plausible mechanistic data linking red and process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 81 publications
2
61
0
3
Order By: Relevance
“…The 2016 IARC Working Group further concluded that the mechanistic evidence for the carcinogenicity was strong for red meat but moderate for processed meat [29]. High iron contents of red meat, particularly heme iron, meat processing resulting in formation of carcinogenic chemicals including N-nitroso-compounds (NOC) and polycyclic aromatic hydrocarbons (PAH), and the production of carcinogens such as heterocylic aromatic amines (HAA) and PAH through high-temperature cooking may account for the association between red and/or processed meat and cancer [29, 30]. However, since inflammation is a key risk factor for cancer [1], our results may suggest that red and/or processed meat consumption could also affect cancer development through the inflammatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The 2016 IARC Working Group further concluded that the mechanistic evidence for the carcinogenicity was strong for red meat but moderate for processed meat [29]. High iron contents of red meat, particularly heme iron, meat processing resulting in formation of carcinogenic chemicals including N-nitroso-compounds (NOC) and polycyclic aromatic hydrocarbons (PAH), and the production of carcinogens such as heterocylic aromatic amines (HAA) and PAH through high-temperature cooking may account for the association between red and/or processed meat and cancer [29, 30]. However, since inflammation is a key risk factor for cancer [1], our results may suggest that red and/or processed meat consumption could also affect cancer development through the inflammatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between meat, overall diet, human physiology (including the gut microbiome), and health outcomes are highly intricate. Within this web of complexity, and in contrast to what is commonly stated in the public domain (Leroy et al, 2018a), the current epidemiological and mechanistic data have not been able to demonstrate a consistent causal link between red meat intake and chronic diseases, such as colorectal cancer (Oostindjer et al, 2014;Turner & Lloyd, 2017). RCTs can play an important role in establishing causal relationships, and generally provide much stronger evidence than that provided by observational data.…”
Section: Intervention Studies Have Not Been Able To Indicate Unambigumentioning
confidence: 86%
“…Secondly, diets are difficult to disentangle from other lifestyle factors. It has been shown that Western-style meat eating is closely associated with nutrient-poor diets, obesity, smoking, and limited physical activity (Alexander et al, 2015;Fogelholm et al, 2015;Grosso et al, 2017;Turner & Lloyd, 2017). Given the fact that health authorities have been intensely promoting the view that meat is unhealthy, health-conscious people may be inclined to reduce intake.…”
Section: Meat and Health: A Shifting Paradigm?mentioning
confidence: 99%
“…In our study, the colorectal cancer frequency was also comparable to the literature. High fat and meat consumption in the region, as well as environmental conditions, could be contributing factors [17,18].…”
Section: Discussionmentioning
confidence: 99%